PERAN MAJELIS PENDIDIKAN DASAR DAN MENENGAH MUHAMMADIYAH DALAM PENGEMBANGAN LEMBAGA PENDIDIKAN DI KABUPATEN KEPAHIANG - Tince Ajeng Yurika; Iis Sugianti; Irwan Fathurrochman; Lukman Asha (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2020)
This study aims to describe the role of the Muhammadiyah Elementary and Secondary Education Council in the Development of Educational Institutions in Kepahiang Regency. This study aims to determine to what extent the role of the Elementary and Secondary Education Council has carried out its duties and functions which are one of the components of the leadership assistant in the Muhammadiyah organization in the field of education. This research method uses a descriptive qualitative approach. with the technique of collecting data from observations, interviews, to the chairman of the Kepahiang District Educational Council and supported by some related literature. The research data is reduced and presented, then analyzed for several conclusions. The results showed that; Providing assistance for learning facilities seeking facilities and infrastructure as well as financing providing facilities for learning activities through sports, scouting and religious activities to support the quality of educational institutions to develop better and superior, improve the quality of human resources for educators through routine training and guidance from relevant agencies and carry out learning evaluations at each educational institution how to view monthly performance reports, this is in accordance with the duties of the Dikdasmen assembly, namely as follows.